Patch Testing of Thai Children with Eczema - Puangpet, Pailin; Boonpuen, Niorn; Saipornchai, Kasira; Suchaoin, Rungrat; Poompakdeepan, Pattarida; McFadden, John (Siriraj Medical Journal, 2023)
Objective: To detect contact allergy rate and common allergens in Thai children presented with eczema. Materials and Methods: A total of 124 children, aged 1-15 years, were patch tested using a pediatric screening series of 16 allergens and relevant additional allergens. Data on clinical presentation, atopic history and test results were collected. Results: Contact allergy was found in 51 of 124 children (41.1%) presented with all forms of eczema. The common allergens were lanolin alcohol (8.9%), cocamidopropyl betaine (8.1%), nickel sulfate (7.3%), fragrance mix I (5.6%), formaldehyde (5.6%), thimerosal (5.6%), fragrance mix II (4.8%), cobalt chloride (4.0%), methylchloroisothiazolinone/methylisothiazolinone (2.4%), methylisothiazolinone (2.4%) and thiuram mix (2.4%). Nineteen of 50 atopic dermatitis patients (38%) showed positive patch test reactions. Conclusion: Allergic contact dermatitis is common in children. Both atopic and non-atopic patients can develop contact dermatitis. Patch testing should be performed in children presented with eczema regardless of contact dermatitis history.